2021
DOI: 10.1101/2021.07.06.451223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ca2+-dependent liquid-liquid phase separation underlies intracellular Ca2+ stores

Abstract: Endoplasmic/sarcoplasmic reticulum Ca2+ stores are essential to myriad cellular processes, however, the structure of these stores is largely unknown and existing models neither explain observations made in vivo nor sufficiently account for physiological data. We investigate CASQ1 - the major Ca2+ binding protein of skeletal muscle - and discover Ca2+-dependent liquid-liquid phase separation activity. The intrinsic disorder of CASQ1 underlies this activity and is regulated via phosphorylation by the secretory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Less is known concerning the ability of polyanionic proteins to undergo LLPS in a similar charge-dependent manner. Mayfield et al identified a previously unknown mechanism of calcium-dependent LLPS occurring within the endoplasmic/sarcoplasmic reticulum (ER/SR) that explains efficient calcium ion buffering and storage [ 44 ]. It was shown that calcium ions modulate LLPS of the polyanionic protein and major calcium-binding protein of the SR of skeletal muscle, calsequestrin-1 (CASQ1).…”
Section: Role Of Proteins and Divalent Ions In Llpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Less is known concerning the ability of polyanionic proteins to undergo LLPS in a similar charge-dependent manner. Mayfield et al identified a previously unknown mechanism of calcium-dependent LLPS occurring within the endoplasmic/sarcoplasmic reticulum (ER/SR) that explains efficient calcium ion buffering and storage [ 44 ]. It was shown that calcium ions modulate LLPS of the polyanionic protein and major calcium-binding protein of the SR of skeletal muscle, calsequestrin-1 (CASQ1).…”
Section: Role Of Proteins and Divalent Ions In Llpsmentioning
confidence: 99%
“…CASQ1 is an IDP that influences its capacity for LLPS. It was also shown that the LLPS of CASQ1 is regulated via phosphorylation by the secretory pathway kinase Fam20C, which phosphorylates structurally-conserved regions of CASQ1 [ 44 ]. Thus, the phosphorylated protein (pCASQ1) more readily entered the LLPS state.…”
Section: Role Of Proteins and Divalent Ions In Llpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging in vivo and cross-linking experiments support the notion that this material is Ca 2+ -complexed CASQ [18][19][20]. In addition, these structures disassemble and disperse under luminal Ca 2+ depletion conditions [15,21], which correlates with the fact that the recombinant protein can organize in vitro into multiple architectures of varying compactness, hierarchically ordered in response to rising Ca 2+ concentrations from micromolar levels up to 20 mM [3,16,17,22] (Figure 2). As higher order polymeric structures are formed, the capacity and cooperativity of Ca 2+ -binding events show a parallel, stepwise increase, which has consequences for the modulation of intra-SR Ca 2+ storage and release.…”
Section: Casq Macro-architecture(s)mentioning
confidence: 60%
“…IDPs often engage in multivalent interactions [60], including those leading to liquid-liquid phase separation [61][62][63]. Emerging research shows that phase separation can be regulated by calcium in the endoplasmic/sarcoplasmic reticula to enable efficient calcium buffering [64]. Taken together, this suggests that the negatively charged IDPs may work to sponge calcium towards the multi-protein complexes, thus regulating calcium bioavailability and signaling.…”
Section: Discussionmentioning
confidence: 99%